Harry N. Sargent papers - Sargent, Harry N.
Correspondence, drafts of Sargent's unpublished book: America's Part in the Great War, notes by Fox Conner on the U.S. Army American Expeditionary Forces, and maps. Correspondents include James G. Harbord.
Library of Congress Prints and Photographs Division.
Library of Congress Geography and Map Division.
British army officer. Full name: Harry Neptune Sargent. Born 1866; died 1946.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Conner, Fox, -- 1874-1951.; Harbord, James G. -- 1866-1947 -- Correspondence; United States. -- Army. -- American Expeditionary Forces; World War, 1914-1918.; Army officers, British